Mechanobiological models of Skeletal Tissue Differentiation - KELLY, DANIEL (Polish Academy of Sciences, 2005)
Mechanical forces may act within tissues at the cellular level to regulate biological processes, a field of study that has been termed mechanobiology. The aim of computational mechanobiology is to derive sets of equations that describe the changes in cell expression, and hence the composition, structure and phenotype of tissues, as a function of the applied mechanical stimuli. This chapter will attempt to review the different mechanobiological models that have been developed to relate mechanical stimuli to tissue differentiation. The majority of these models have been used to simulate tissue differentiation during fracture healing or osteochondral defect repair. Based on this review, a number of recommendations will be made by the author for the future development of computational models of tissue differentiation.
PUBLISHED
Keywords: Mechanobiology; Tissue Differentiation; Finite Element Model; Fracture Healing; Osteochondral defect repair